2013
DOI: 10.1002/pbc.24482
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheters and catheter locks in children with cancer: A prospective randomized trial of taurolidine versus heparin

Abstract: Background To determine if the catheter lock taurolidine can reduce the number of catheter‐related bloodstream infections (CRBSI) in pediatric cancer patients with tunneled central venous catheters (CVC). Procedure During a study period of 34 months, 129 newly placed tunneled CVCs in 112 patients were randomly assigned to standard lock with heparin solution or experimental lock with a taurolidine solution (http://ClinicalTrials.gov Identifier NCT00735813). Results Sixty‐five CVCs were included in the standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 33 publications
2
48
1
Order By: Relevance
“…In the ATAPAC trial, the TIVAP-RI inci- 104 dence rate of both groups is consistent with the literature data reporting a rate from 0.11 to 1.45‰ catheter-days [4,[13][14][15][16][17] . Despite a relative risk reduction of 4 times by TauroLock, this difference was not statistically significant because the TIVAP-RI incidence rate observed in the control group was significantly lower than the one chosen as reference of 3‰ catheter-days for sample size calculation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the ATAPAC trial, the TIVAP-RI inci- 104 dence rate of both groups is consistent with the literature data reporting a rate from 0.11 to 1.45‰ catheter-days [4,[13][14][15][16][17] . Despite a relative risk reduction of 4 times by TauroLock, this difference was not statistically significant because the TIVAP-RI incidence rate observed in the control group was significantly lower than the one chosen as reference of 3‰ catheter-days for sample size calculation.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have confirmed an important activity of TauroLock in TIVAP-RI prevention in high-risk patients [10][11][12][13] . In the ATAPAC trial, the TIVAP-RI inci- 104 dence rate of both groups is consistent with the literature data reporting a rate from 0.11 to 1.45‰ catheter-days [4,[13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mean cost of the use of thrombolytic treatment with urokinase decreased by 45% during the TCHLS phase compared with the previous phase of heparin lock. Regarding CRBSI, several studies have shown the efficacy of TCHLS in preventing this complication in patients with cancer and in those receiving home parenteral nutrition or hemodialysis (22)(23)(24), with a low risk of resistance development (25). Handrup et al (26) showed that taurolidine significantly reduced the incidence of CRBSI compared with heparin lock but that there was no statistically significant difference in biofilm formation measured by scanning electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another possibility described is taurolidine lock, which, compared to heparin, is significantly more expensive. 19 Partial dysfunction of the central venous catheter is common. Fluids can be infused into the catheter, but blood cannot be aspirated.…”
Section: Discussionmentioning
confidence: 99%